Friendship, the Family and Liturgy: A Rite for Blessing Friendship in Traditional Christianity. Issue 13 (15th January 2013) - Bray, Alan
Abstract : In this paper Alan Bray takes us back to the work of John Boswell on the liturgical marking of friendship in the Greek Church during the Middle Ages. He begins by noting the work that has also been undertaken on the equivalent rite in the Latin west. Much of this work, however, leaves open the question of the purpose of the rite and its use within mediaeval society. Alan Bray looks at a number of theories which have been put forward and then suggests that we cannot read back into the historical situation our own contemporary concerns. He ends the paper by proposing that we need to look at the theological context of the rite and by doing this, he shows that a theological reading allows us to work around the ethical issues. Finally, he proposes this theological approach as a way of linking the mediaeval past with the contemporary situation.